Polariser l'écart : la mise en scène du décalage dans Fram de Tony Harrison - Catherine Lanone (Sillages Critiques)
Polar opposites: discrepancy in Tony Harrison's Fram: Proud of his origins, Tony Harrison blends in his work the memory of his working-class background and of the vast literary tradition he descends from, from Greek tragedy to Shakespeare or Keats. Best known as a poet, Tony Harrison is also a translator and playwright; his 2008 play Fram was badly received by critics, perhaps because it plays on key structural discrepancy, embedding as it does the story of Nansen, the polar explorer (with the eponymous boat he designed, Fram) within the frame of a play written by the ghost of the late academic Gilbert Murray. The mixture of tones and genres, of grand visual special effects, of burlesque, deliberately badly written verse attributed to Murray and of poignant, tragic moments (such as the speech about starvation in Russia) may well be problematic, but the play may be better understood when placed in the context of the myth of Polar exploration haunting Victorian Britain. Harrison revisits the Arctic myth, debunking heroic codes, yet using the Arctic as a fitting metaphor to raise historical and contemporary ethical questions, leading from the tragic mask to the Fram, an emblem of tolerance and survival.